PERAN LEMBAGA ADAT DALAM PENGELOLAAN DAYA TARIK PARIWISATA WAEREBO DI PROVINSI NUSA TENGGARA TIMUR - Dahom, Avelina; Ranteallo, Ikma Citra; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Waerebo is one of the traditional institutions located in the village Satarlenda, District Satarmese West Manggarai regency, East Nusa Tenggara Province. Waerebo customary institutions have very interesting potential for tourists, namely the potential of natural and artificial potential also very beautiful natural scenery and managed by the communities themselves Wearebo. Tourism attraction in Waerebo are custom homes that are very interested by tourists who shaped Krucut and have five levels, when tourists go to Waerebo, the person in charge of serving travelers to wear customs such as: "towe songke, scarves songke, and broom songke ". Key word: Traditional Institutions, Tourism, Empowerment.